Arthropods on Platycyamus regnellii (Fabaceae) leaf surface: indice and ecological relationships. Technical Note - Leão Demolin-Leite, G.; Valenciaga, Nurys; Ferreira Santos Guanabens, Patrícia; Alvarenga Soares, M.; Silva, Júlia Letícia; Nunes Gomes, Gleisiany; Cola Zanuncio, J. (Cuban Journal of Agricultural Science, 2023)
Platycyamus regnellii is a Brazilian tree used in landscaping, degraded area recovery, and its wood for furniture. It is evaluated the ecological indices and interactions between the groups of arthropods on P. regnellii leaf surface. Highest numbers of phytophagous arthropods Orthoptera Tettigoniidae and Tropidacris collaris (Romaleidae), and Hemiptera Pentatomidae; natural enemies Hymenoptera Camponotus sp. and Pseudomyrmex termitarius (Formicidae), and Diptera Dolichopodidae; and abundance and species richness of chewing insects and protocooperating ants were observed on the adaxial leaf face of P. regnellii plants. Abundance of spiders correlated, positively, with that of chewing insects and number of spiders with that of T. collaris. The knowledge of the leaf face, preferred by herbivorous insects, helps in the correct application of pesticides in integrated pest management programs. Key words: abundance, diversity, species richness, sucking insects